(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article reflects unusual combinations and their use in linguistics, their place in the linguopoetic analysis of literary texts, and the scientific views of Nizomiddin Mahmudov on unusual combinations, examples of unusual combinations used in artistic texts are presented.